2021
DOI: 10.3390/polym13101651
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Copolymerization of Cyclohexene Oxide and Cyclic Anhydrides Catalyzed by Bimetallic Scorpionate Zinc Catalysts

Abstract: The catalytic activity and high selectivity reported by bimetallic heteroscorpionate acetate zinc complexes in ring-opening copolymerization (ROCOP) reactions involving CO2 as substrate encouraged us to expand their use as catalysts for ROCOP of cyclohexene oxide (CHO) and cyclic anhydrides. Among the catalysts tested for the ROCOP of CHO and phthalic anhydride at different reaction conditions, the most active catalytic system was the combination of complex 3 with bis(triphenylphosphine)iminium as cocatalyst i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Given the challenge of preparing new bio-based materials, other cyclic anhydrides, such as MA and SA, were used as starting materials together with EOO to obtain the corresponding poly­(EOO- co -MA) and poly­(EOO- co -SA) polyesters, respectively (Table ). It is reported that in some cases for both MA and SA, there are more difficulties in the formation of polyesters by the ROCOP process. , However, under relatively moderate reaction conditions, MA and SA anhydrides have also been used as substrates for the creation of various polyesters, which is directly related to the activity of the applied catalytic systems. , Additionally, Thumrongpatanaraks et al observed a notable difference in the reactivity between MA and SA with propylene oxide (PO) when using the same bis­(amidinate)­tin­(II) catalyst where the poly­(PO- co -MA) polyester was afforded at 80% conversion in only 1 h, whereas SA required 8 h to form poly­(PO- co -SA) with a similar conversion . In our case, the successful preparation of poly­(EOO- co -MA) was performed under the same reaction conditions as poly­(EOO- co -PA), although the synthesis of poly­(EOO- co -SA) required more extreme reaction conditions (reflux in toluene for 72 h), as can be seen in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the challenge of preparing new bio-based materials, other cyclic anhydrides, such as MA and SA, were used as starting materials together with EOO to obtain the corresponding poly­(EOO- co -MA) and poly­(EOO- co -SA) polyesters, respectively (Table ). It is reported that in some cases for both MA and SA, there are more difficulties in the formation of polyesters by the ROCOP process. , However, under relatively moderate reaction conditions, MA and SA anhydrides have also been used as substrates for the creation of various polyesters, which is directly related to the activity of the applied catalytic systems. , Additionally, Thumrongpatanaraks et al observed a notable difference in the reactivity between MA and SA with propylene oxide (PO) when using the same bis­(amidinate)­tin­(II) catalyst where the poly­(PO- co -MA) polyester was afforded at 80% conversion in only 1 h, whereas SA required 8 h to form poly­(PO- co -SA) with a similar conversion . In our case, the successful preparation of poly­(EOO- co -MA) was performed under the same reaction conditions as poly­(EOO- co -PA), although the synthesis of poly­(EOO- co -SA) required more extreme reaction conditions (reflux in toluene for 72 h), as can be seen in Table .…”
Section: Resultsmentioning
confidence: 99%
“…It is important to highlight that this novel synthetic route has not been previously reported to date using olive-based epoxidized vegetable oils as precursors. , The first synthetic approach has been recently published by Kleij et al, where the preparation of attractive functional bio-polyesters has been achieved from the reaction between fatty acid epoxides and cyclic anhydrides . This ROCOP reaction has been extensively investigated with commercially available cyclic epoxides and anhydrides, although it requires the presence of a metal catalyst or an organocatalyst. In recent years, organocatalysts have become more popular than metal catalysts, since metal-free catalysts offer several advantages, such as higher catalyst availability at lower costs, lower sensitivity to oxygen or water, and they are more ecological and less toxic than metal-containing catalysts …”
Section: Introductionmentioning
confidence: 99%
“…The molecular weight of the polyester from entry 6 was unusually high in comparison to those reported in the literature for poly­(PA- alt -CHO), which normally ranged from 10 to 20 kg/mol. Moreover, the T g (145 °C; Figure S13) was also higher than those of previously reported poly­(PA- alt -CHO) (135–144 °C). , …”
Section: Resultsmentioning
confidence: 56%
“…In agreement with these expectations, poly(NA-alt-CHO) obtained showed a T g of 180 °C (Figure S14), which is considerably high compared to the typical T g (140−208 °C) reported in the literature (Figure 3). 15,16,19,30 Changing the cocatalyst to PPNCl resulted in a very low conversion (2%) and poor selectivity (34% ester content) under the same reaction conditions, probably due to the bulkiness of both NA and PPNCl. When the reaction time was extended, the conversion was slightly improved to 14% in 72 h (entry 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5 Among all combinations, polyesters have shown their superiority, especially due to the high levels of structure–property tuneability control achieved during the ring-opening copolymerization (ROCOP) reaction. 6 Nevertheless, the major challenge of those synthetized polyesters is their poor optical properties, as they do not have any traditional chromophore ( e.g. the absence of polycyclic non-aromatic molecular structures) which can absorb in the visible and near-infrared spectral regions.…”
Section: Introductionmentioning
confidence: 99%